A nomeação como procedimento de constituição da identidade negra nos discursos sociais e nos documentos oficiais do Estado: um silenciamento da miscigenação - Luz, Marcelo Giovannetti Ferreira (2011)
This thesis, titled Naming as a procedure for setting up of black identity in social discourse and official documents of the State: a silencing of miscigenation, aims to analyse the formation of a new black identity in modern society, due to the clustering of mixed identities, which are mulatto, cafuzo, among many others arising from the cultural mix in which Brazil went on, and pass overall these years of its existence. Therefore, we sought to examine how the imposition of new ways of naming these individuals produce a movement towards its identity, which is misplaced in the sense of being subsumed by the black identity. Therefore, we analysed the procedures for rewriting, in order to examine how these names are rewritten in oficial state documents and interviews we have collected about black identity in magazines aimed at black audiences, such as Raça Brasil. Furthermore, we understand the movement of meaning of these identities in oficial documents as A Cartilha do Politicamente Correto, o Estatuto da Igualdade Racial and some dictionaries circulating more frequently in society, as well as electronic enciclopedias that have a much greater access than the common dictionaries for they are available on the network. As a way to check the directions that some meanings move in such speeches, we analyse the discoursive memory that these lexicons have, when circulating in certain areas regulated by specific ways of saying, therefore, we understand their production since the arrival of Europeans to Brazil and his contact with the native, naming him according a memory typically Eurocentric, and the appointment of Africans, which produces effects of meaning that will be recollected in later events. As a central event that causes our studies, we have the discussions about the deployment of ethnic and racial quotas for admission to public universities in Brazil. Such event gives rise to new meanings about the black as well as directions that will be recollected, such as prejudice, and others will be deleted, as the mixing of cultures. Thus, we can see that there is a policy of silence on certain names, preventing the subjects designated by other places to occupy another places to say, banning this subjects-positions in society that is regarded as democratic one.